Effect of electron beam irradiation on the thermal, mechanical and aging behaviors of polyethylene/carbon black nanocomposite. (October 2021) - Akhavan, A.; Khoylou, F.; Sheikh, N.; Kazeminejad, H.
Abstract: In this paper effect of electron beam irradiation on the thermal, mechanical and aging behaviors of polyethylene containing nanosized carbon black (PE/CB) was investigated to find its potential applicability as an absorber material for solar thermal collectors. SEM images obtained before irradiation of PE/CB nanocomposite containing 2.25 wt% CB, proved a good dispersion of CB in polymer matrix. PE/CB samples were irradiated by electron beam at doses ranging from 100 to 200 kGy. The results obtained from both the gel–sol and the hot set analyses show that the degree of crosslinking, subsequently thermal stability, is dose-dependent. The best mechanical properties were observed for PE/CB sample crosslinked at 100 kGy. From the Differential Scanning Calorimetry (DSC) analysis it was found that thermal aging of 100 kGy irradiated sample in hot air at 140 °C for 100, 200 and 400 h causes a prominent increase in melting point and degree of crystallinity during initial 100 h, followed by a slower increase at longer aging times. In addition, decreasing the oxidation temperature (Tox ) values show that during thermal aging chemical changes occur in the irradiated sample. A slightly increase in carbonyl index (CI) displays fairly degradation after 400 h aging time. The solar thermal absorbance is nearly independent of radiation crosslinking of PE/CB. Highlights: Thermal stability of the PE/CB nanocomposite improved by radiation crosslinking. The best mechanical properties were observed for PE/CB crosslinked at 100 kGy. Thermal aging causes an increase in melting point and crystallinity of XPE/CB. Radiation crosslinked PE/CB is a promising candidate for solar thermal collectors.